Devolution of healthcare system in Kenya: progress and challenges - Masaba, B.B.; Moturi, J.K.; Taiswa, J.; Mmusi-Phetoe, R.M. (Public health (London), 2020)
The aim of the present study was to systematically review the progress and challenges on the devolved healthcare system in Kenya. A systematic review design was adopted for the present study. Literature search was on biomedical databases of the most recent available electronic data published in English, that is, between January 2012 and April 2020. The populations for eligible studies were stakeholders within the county governments, healthcare workers and community dwellers. The databases included PubMed, EMBASE and Google Scholar. The following were the key words used in the search: ‘Devolution of Health’ ‘Health care system in Kenya’ AND ‘County Health Facilities’ ‘challenges’ AND ‘progress’ AND ‘Kenya’. Other literature sources were after screening of all the references of all the added articles. Before the development of search terms, we looked for appropriate Medical Subject Headings terms and applied with maximal truncations. The data were qualitatively analysed, and findings were presented by three thematic domains. The search generated 1109 articles, of which 23 articles met the inclusion criteria. Data were presented and organized under three thematic domains: (1) localised decision-making process, (2) improvement in structural development and (3) inadequate resources/funds/staff. This is a systematic review which, to the best of our knowledge, is the first study of its kind to present the available evidence on the progress and challenges on the devolved healthcare system in Kenya. The major findings of this review were as follows: there was improvement in the health structural development that was brought by devolution in the country. However, devolution is not free of challenges. The major challenges noted in the postdevolution era within the health sector include inadequate resources/funds from the national government and understaffed health facilities. The study recommends allocation of resources to counties commensurate with the devolved functions. The study calls out for further research on equity and equality of the devolved healthcare system in Kenya. What is known?•Devolution is a form of decentralization or the transfer of authority and responsibility from central to lower levels of government for a range of public functions.•In 2013, Kenya transitioned into a devolved system of governance comprising two levels: the national government and 47 semiautonomous county governments.•Under devolution, the health service delivery function was transferred to county governments while the national government retained policy and regulatory functions.What is new?•There was improvement in health structural development that was brought by devolution in the country.•The major challenges noted in the postdevolution era within the health sector include inadequate resources/funds from the national government and understaffed health facilities.•The study recommends allocation of resources to counties commensurate with the devolved functions.•The study calls out for further research on equity and equality of the devolved healthcare system in Kenya.